(untitled) (IPS Journal of Toxicology, 2025)
This study assessed the levels of PTEs in surface water and sediment from Orosikiri and Akiama, two communities along the Bonny River, Nigeria. Surface water and sediment samples were collected and analyzed for physicochemical parameters and PTE concentrations. The study also evaluated human health risks using the estimated daily intake (EDI), target hazard quotient (THQ), and carcinogenic risk (CR) models. Results showed that physicochemical parameters such as temperature (25.30–25.80°C), pH (6.36–6.74), and electrical conductivity (43.69–74.95 µScm-l) were within permissible limits. However, total dissolved solids (TDS) (44.97–45.97 mgL-l), chemical oxygen demand (COD) (50.87–74.69 mgL-l), and biological oxygen demand (BOD) (8.34–13.08 mgL-l) exceeded WHO/USEPA standards. Water Quality Index (WQI) values ranged from 147.38 to 193.25, classifying the water as unfit for consumption. PTE concentrations in surface water samples were higher in Orosikiri, with Pb (1.9887 mgL-l), Cd (0.154 mgL-l), and Cr (5.0087 mgL-l) exceeding safety limits. Risk Quotient (RQ) values for PTEs in water were below 1, suggesting no immediate risks to aquatic life. Pearson correlation analysis indicated common pollution sources for Pb, Cd, and Cr, likely from industrial and oil-related activities. Human health risk assessments revealed that the EDI of Pb, Cd, and Cr exceeded WHO limits, with children at greater risk. Carcinogenic risk (CR) values for As and Cr exceeded the acceptable threshold (10⁻⁴), signaling long-term cancer concerns. These findings underscore the need for continuous monitoring of pollution control measures and remediation strategies to mitigate contamination risks and protect public health.